Etika Konselor Profesional dalam Bimbingan dan Konseling - Tumanggor, Athalia A. Aptanta; Jamaris; Solvema (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
Every people in their life must be preoccupied with all kinds of activities and surely every activity is carried out has a good effect or can make a problem. A counsellor as a professional in Guidance and Counseling by having a specific object to helping and development an effective daily life and handling that effective life to individual or client must being prepared when that client trust the expert to help and handle every problem. In that execution a counsellor must apply and uphold ethics and values counsellor must have consciousness to do a good job in order to upgrading client trust so can help development and solve the problem.